2017
DOI: 10.1002/jctb.5371
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydrophobicity and acidity effect on alumina catalyst in catalytic methanol dehydration reaction

Abstract: BACKGROUNDMethanol to dimethyl ether (MTD) is considered one of the main routes for the production of clean bio‐fuel. The effect of copper loading on the catalytic performance of different phases of alumina that formed by calcination at two different temperatures was examined for the dehydration of methanol to dimethyl ether (DME).RESULTSA range of Cu loadings of (1, 2, 4, 6, 10 and 15% Cu wt/wt) on Al2O3 calcined at 350 and 550 °C were prepared and characterized by TGA, XRD, BET, NH3‐TPD, TEM, H2‐TPR, SEM, ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…2b which is in agreement with the kinetic model shown in Table 2. Moreover, during the reaction mechanism, water is produced which has a significant effect on the alumina catalyst deactivation, as water and methanol compete for adsorbing on the active sites of alumina catalyst with water being adsorbed more strongly [31]. It is worth noting that in our previous publication we showed that the prepared η-Al 2 O 3 has similar morphology and surface acidity of zeolite [HZSM-5(80)] which is in line with the fitted kinetic modelling as our work matched with Lu model who studied the kinetic modelling of zeolite as shown in Table 2 [10].…”
Section: Validation Of the Kinetic Modelmentioning
confidence: 99%
“…2b which is in agreement with the kinetic model shown in Table 2. Moreover, during the reaction mechanism, water is produced which has a significant effect on the alumina catalyst deactivation, as water and methanol compete for adsorbing on the active sites of alumina catalyst with water being adsorbed more strongly [31]. It is worth noting that in our previous publication we showed that the prepared η-Al 2 O 3 has similar morphology and surface acidity of zeolite [HZSM-5(80)] which is in line with the fitted kinetic modelling as our work matched with Lu model who studied the kinetic modelling of zeolite as shown in Table 2 [10].…”
Section: Validation Of the Kinetic Modelmentioning
confidence: 99%
“…Alumina can also adsorb heavy metals where its surface area can reach 369 m 2 /g [17][18][19] but again this is proving too expensive for developing countries. Alumina can also adsorb heavy metals where its surface area can reach 369 m 2 /g [17][18][19] but again this is proving too expensive for developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…There are many traditional processes for removing heavy metals from wastewater depending on chemical precipitation, floatation, adsorption, ion exchange, and electrochemical deposition. Alumina can also adsorb heavy metals where its surface area can reach 369 m 2 /g [17][18][19] but again this is proving too expensive for developing countries. Researchers in developing countries suggest the use of adsorbents produced from agricultural waste materials [20] such as spent grain [21], aquatic weeds [22], egg shell [23], coal fly ash [24][25][26], rice husks [27], and polymerized onion skin [28] could become economically viable for HMR process.…”
Section: Introductionmentioning
confidence: 99%
“…Thepublications observed on protonation of Brønstedacid sites induce hydrogen ions for rebranching and isomerisation processes in high Si/Al zeolites [10][11][12][13][14][15][16][17][18]. The previous study revealed that zeolite makes the transition metal more electrophilic, thus helps the reoxidation of metal during the reaction [19].…”
Section: Parametersmentioning
confidence: 92%
“…Hydrotreated FAME in Gas Oil ( In recent decades, hydro-isomerisation of ULSD by noble metals on acidic solid catalyst like zeolites or silica aluminates in micro-or mesopore structure was used in refineries [6][7][8][9]. Zeolite synthesis with different crystalline structure and characteristics had widely studied and, its performance was investigate using hydro-isomerisation and hydrocracking on ZSM, Y-type, H-β, SAPO and MCM for branching the high molecular weight straight-chain hydrocarbons [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Product shape selectivity mainly achieved through the crystalline pore structure and molecule size in pore diffusive diameter, but the acidity of catalyst play the main role in product distribution [13][14][15].The tuning of the acidic property of zeolite and extrudate was achieved by varying SiO 2 /Al 2 O 3 (or Si/Al) and the operating temperature.…”
Section: Parametersmentioning
confidence: 99%